2014
DOI: 10.1176/appi.ajp.2014.13111464
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Face and Gaze Habituation in Fragile X Syndrome

Abstract: Objective We sought to investigate neural system habituation to face and eye gaze in fragile X syndrome (FXS), a disorder characterized by eye gaze aversion, among other social and cognitive deficits. Method Participants (age 15-25 years) included 30 individuals with FXS (14 females) and a comparison group of 25 individuals without FXS (12 females) matched for general cognitive ability and autism symptoms. We used fMRI to assess brain activation during a gaze habituation task. Participants viewed repeated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 37 publications
2
46
1
Order By: Relevance
“…This increase shows an abnormal pattern of habituation as suggested by auditory studies. Also, it would be in line with (Bruno et al, 2014), who found sensitization in the FXS group, indicating deficient modulation of neural responses to repeated gaze stimuli. In visual sensory ERP and an oddball paradigm using smiley faces, larger N1 and N2b amplitudes and reduced P3b amplitudes are found in FXS patients (Knoth et al, 2014; Van der Molen et al, 2012b).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This increase shows an abnormal pattern of habituation as suggested by auditory studies. Also, it would be in line with (Bruno et al, 2014), who found sensitization in the FXS group, indicating deficient modulation of neural responses to repeated gaze stimuli. In visual sensory ERP and an oddball paradigm using smiley faces, larger N1 and N2b amplitudes and reduced P3b amplitudes are found in FXS patients (Knoth et al, 2014; Van der Molen et al, 2012b).…”
Section: Discussionsupporting
confidence: 88%
“…They found significantly greater decrease in N1 ERP component amplitude and inter‐trial coherence (ITC) in lower frequency bands with repetitions in controls than in patients, suggesting a stronger habituation for controls. Only Bruno and colleagues addressed this issue in the visual modality using fMRI (Bruno et al, 2014). They presented four unique repeated faces with either direct or averted eye gaze and participants (controls and patients) had to judge the direction of eye gaze.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the processing problem are difficulty tolerating bright lights and loud noises, crowded places overstimulation, difficulty making good eye contact, and trouble tolerating certain clothes. These problems are related to a lack of normal habituation to a sensory stimulus seen in both electrodermal studies (145) and even on Functional Magnetic Resonance Imaging (fMRI) studies to recurrent direct or indirect eye contact (146).…”
Section: Other Problemsmentioning
confidence: 99%
“…The team can be adjusted for each individual's problems. There are many tools that have been proven useful and reliable for assessing an individual's condition such as the Sensory Profile questionnaire, the Sensory Processing Measure questionnaire, the Movement Assessment Battery for Children, the Quick Neurological Screening Test and the Berg Balance Scale (146). It is recommended that children with FXS should receive routine assessments from occupational therapists and receive occupational therapy at least twice a week during early development (66).…”
Section: Other Problemsmentioning
confidence: 99%
“…It is possible that these results were a reflection of compromised capacity in processing facial information, which is potentially consistent with the small size of the amygdala in individuals with FraX (15, 16). In addition to the amygdala, abnormal habituation was also found in the anterior cingulate, fusiform gyrus, as well as frontal cortex of young adults and adolescents with FraX when responding to face/eye gaze (37). Finally, individuals with FraX have decreased duration of eye fixation, which is putatively associated with decreased activation of FFA (38).…”
Section: Fragile X Syndrome – a Complex Neuropsychiatric Diseasementioning
confidence: 99%